2004
DOI: 10.1016/j.ijgo.2004.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin and vascular endothelial growth factor in pregnancies complicated by preeclampsia

Abstract: Elevated levels of both VEGF and angiogenin could confirm the existence of vascular reactivity and endothelial disturbance in preeclampsia. Measurement of these angiogenic factors in maternal serum may be a useful as biomarkers for the assessment of the severity of the disease and of fetal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…It has been suggested that the vascular and nervous systems are functionally and structurally different but they share some multiple similarities in their development, construction, and function (Pucci et al, 2008). Recent studies suggest that dysregulation of angiogenic factors and their soluble fms‐like tyrosine kinase‐1 receptors (sFlt‐1) play an important role in the pathogenesis of pre‐eclampsia although the results are inconsistent (Laskowska et al, 2008; Shaarawy et al, 2005; De Vivo et al, 2008). It is suggested that sFlt‐1 and PlGF could together serve as predictors of pre‐eclampsia (Levine et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the vascular and nervous systems are functionally and structurally different but they share some multiple similarities in their development, construction, and function (Pucci et al, 2008). Recent studies suggest that dysregulation of angiogenic factors and their soluble fms‐like tyrosine kinase‐1 receptors (sFlt‐1) play an important role in the pathogenesis of pre‐eclampsia although the results are inconsistent (Laskowska et al, 2008; Shaarawy et al, 2005; De Vivo et al, 2008). It is suggested that sFlt‐1 and PlGF could together serve as predictors of pre‐eclampsia (Levine et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…4 Recent studies suggest that dysregulation of angiogenic factors and their soluble fmslike tyrosine kinase-1 receptors (sFlt-1) has an important role in the pathogenesis of preeclampsia, but the results are inconsistent. Although some studies report lower plasma vascular endothelial growth factor (VEGF) levels 5 in preeclamptic women compared with normotensive women, [6][7][8][9] other studies report higher levels in preeclamptic women, 10,11 and some found no difference between the two groups. 5 Placental growth factor (PlGF) is a placental protein that potentiates the effect of VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…A finding that was reported by a number of groups (Reuvekamp et al, 1999;Koga et al, 2003;Polliotti et al, 2003;Tsatsaris et al, 2003). In the contrast, also several studies exist, which described rising VEGF protein levels in the patients serum (Kupferminc et al, 1997;Shaarawy et al, 2005) or umbilical cord blood (Galazios et al, 2004).…”
Section: Preeclampsiamentioning
confidence: 82%